2021
DOI: 10.1007/s12016-021-08842-9
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Immune Cells in Hereditary Angioedema

Abstract: Hereditary angioedema (HAE) is a rare genetic disease, characterized by recurrent and unexpected potentially life-threatening mucosal swelling. HAE may be further classified into HAE with C1‐inhibitor deficiency (C1‐INH‐HAE) and HAE with normal C1‐INH activity (nlC1‐INH‐HAE), mostly due to mutations leading to increased vascular permeability. Recent evidence implicates also the innate and adaptive immune responses in several aspects of angioedema pathophysiology. Monocytes/macrophages, granulocytes, lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 160 publications
0
9
0
2
Order By: Relevance
“…Adaptive immunity has not been thoroughly analyzed in HAE pathogenesis. A few studies show alterations in T-cell profiles and/or cytokine production [ 5 ] . On the other hand, it has been observed that adaptive immune responses may be involved in the development of autoimmune disease in patients with HAE, mainly through alterations in B-cell activation and survival [ 3 , 6 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive immunity has not been thoroughly analyzed in HAE pathogenesis. A few studies show alterations in T-cell profiles and/or cytokine production [ 5 ] . On the other hand, it has been observed that adaptive immune responses may be involved in the development of autoimmune disease in patients with HAE, mainly through alterations in B-cell activation and survival [ 3 , 6 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Disruption in the number of lymphocytes when comparing HAE patients and healthy subjects can be somehow surprising. Since the cells mediate adaptive immune responses, they seem to be uninvolved in HAE [ 17 ]. Only a few studies have reported abnormal T and B cell counts or abnormal distribution of T cell surface IgG-receptors [ 18 , 19 ].On the contrary, the study from Lopez-Lera et al on the profiling of the RNA expression of peripheral blood mononuclear cells (PBMC) from C1-INH-HAE patients did not prove alterations in the expression pattern of PBMC in association with frequency and severity of disease [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Probably, the HAE attack duration can be altered by the cross-play between immune cells producing vasoactive mediators, including bradykinin, histamine, complement components, or vasoactive mediators. Such molecules activate certain immune cell subtypes contributing to vascular endothelial processes that lead to hyperpermeability and tissue edema [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Таким образом, допускается существование нескольких локальных факторов, стимулирующих выработку брадикинина в конкретном месте, в частности в мягких тканях лица, рук, ног, гениталий, а также на слизистых оболочках, выстилающих дыхательный и пищеварительный тракты [23]. Выдвигают предположения о вовлеченности врожденной и адаптивной иммунной системы в ангиоотек [15]. Так, моноциты, макрофаги, гранулоциты, лимфоциты, базофилы, эндотелиальные клетки прямо или косвенно могут участвовать в иммунопатогенезе ангиоотека.…”
Section: Discussionunclassified
“…В частности, была показана положительная корреляция между повышенными значениями уровня фактора роста эндотелия сосудов (VEGF), продуцируемого различными клетками, в том числе эндотелиальными, и тяжестью течения НАО [21]. В дополнение к этому, макрофаги секретируют широкий спектр медиаторов, включая компоненты комплемента, такие как C1-INH, который, как известно, является ключевым фактором развития НАО [15]. Возможно также носительство мутаций в генах, которые оказывают негативный синергический эффект на развитие и течение НАО, что косвенно подтверждается различными триггерами данного заболевания (колебания уровней гормонов, в первую очередь эстрогена, ингибиторы ангиотензин-превращающего фермента (ACI), травма, манипуляции с верхними дыхательными путями и медицинские процедуры, в том числе хирургическое и стома-тологическое вмешательство, эмоциональный стресс, инфекции) [13].…”
Section: Discussionunclassified